ChemInform Abstract: Engaging Allene‐Derived Zwitterions in an Unprecedented Mode of Asymmetric [3 + 2]‐Annulation Reaction. Issue 50 (November 2016) - Sankar, Muthukumar G.; Garcia‐Castro, Miguel; Golz, Christopher; Strohmann, Carsten; Kumar, Kamal
Abstract: The addition of a chiral spiro phosphine catalyst to an α‐substituted allene ester generates a zwitterionic dipole, which can engage isatine‐derived N‐Boc‐ketimines in a novel mode of [3 + 2] annulation.